A Bibliometric Analysis of Marketing 4.0 Literature - Suman Kamal Parajuli (Lembaga Yasin AlSys, 2025)
Marketing 4.0 reflects a shift in marketing practices driven by digital technologies. Understanding the academic contributions to this field through bibliometric analysis helps track its evolution and highlights key areas such as AI, big data, and consumer behavior. A systematic literature review was conducted, analyzing 413 articles from the Dimension AI database. The data was processed using Wordshift for keyword visualization and VOSviewer for bibliographic coupling and network analysis. The study shows significant growth in Marketing 4.0 research, peaking at 112 publications in 2023. Key contributors include authors like Kwon and Sung, and institutions like Kyung Hee University. Indonesia leads in publication output, with prominent keywords like